The Effect of Aflatoxin on the Number, Diameter and Distribution of Hydatid Cyst in Mice - S.S. Aghwan (The Indian Veterinary Journal, 2024)
We carried out this investigation to demonstrate the impact of aflatoxin contamination of diet and its connection to escalating the severity of hydatid cysts in mice. In order to do this, Swiss mice were employed in this investigation, divided into 3 groups of 8 mice each. The first group served as the control group and received no therapy. A single intraperitoneal injection of about 0.2 ml of the medium containing the protoscoleces, approximately 2000 units, was given to the second and third groups. The second group had a regular diet that was comparable to the diet of the control animals, whereas the third group received a daily addition of 1 ppm of aflatoxin B toxins to its diet. The procedures ran continuously for 30 days .In contrast to the non-aflatoxin-diet group, the aflatoxin-diet group had a significantly higher number of hydatid cysts, and a significantly high percentage of cysts with a diameter of (0.3 mm) was found in comparison to the non-aflatoxin-diet group. The distribution of hydatid cysts in the various organs did not differ significantly between the two groups that received aflatoxin treatment and those that did not. We draw the conclusion that aflatoxin contamination of feed plays a significant and decisive role in the spread and severity of Echinococcosis parasites because it was discovered that mice fed a diet with aflatoxin had more parasitoid cysts, which were larger and more prevalent in various organs than the group of mice, not fed diet with aflatoxin.